Deciphering Influence on Social Media: A Comparative Analysis of Influential Account Detection Metrics in the Context of Tobacco Promotion - Alex Kresovich; Andrew H. Norris; Chandler C. Carter; Yoonsang Kim; Ganna Kostygina; Sherry L. Emery (Social Media + Society, 2024)
Influencer marketing spending in the United States was expected to surpass $6 billion in 2023. This marketing tactic poses a public health threat, as research suggests it has been utilized to undercut decades of public health progress—such as gains made against tobacco use among adolescents. Public health and public opinion researchers need practical tools to capture influential accounts on social media. Utilizing X (formerly Twitter) little cigar and cigarillo (LCC) data, we compared seven influential account detection metrics to help clarify our understanding of the functions of existing metrics and the nature of social media discussion of tobacco products. Results indicate that existing influential account detection metrics are non-harmonic and time-sensitive , capturing distinctly different users and categorically different user types. Our results also reveal that these metrics capture distinctly different conversations among influential social media accounts. Our findings suggest that public health and public opinion researchers hoping to conduct analyses of influential social media accounts need to understand each metric’s benefits and limitations and utilize more than one influential account detection metric to increase the likelihood of producing valid and reliable research.